A new marker of risk for ischemic events. (2nd May 2022) - Ferraz, LM; Faustino, A; Carvalho, P; Carvalho, D; Pacheco, A; Viana, J; Neves, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Although dobutamine stress echocardiography (SE) has a high specificity, there is still a subset of patients (P) with false positive tests (FP) and their prognosis remains unclear. Purpose: To identify the clinical and echocardiographic predictors of FP on SE and to evaluate the prognostic impact of FP on SE. Methods: Retrospective study of 355 consecutive adult P who underwent SE for ischemia assessment over a one-year period: 134 (37, 7%) women, 70, 3 ± 0, 57 years, body surface area (ASC) 1, 85±0, 01 cm2. Demographics, risk factors, clinical and laboratorial parameters and SE variables were evaluated. A FP result was defined as a positive SE for ischemia in the absence of ≥50% coronary artery (CA) lesion in a major artery of the corresponding coronary territory on subsequent angiography. P were divided into 2 groups regarding the presence (FP+) or the absence (FP0: 15, 5% true positives, 79, 7% true negatives, 0, 3% false negatives ) of a FP result on SE and a comparative analysis was performed in order to characterize the groups and identify potencial predictors of FP results. P were followed for 2 years to assess acute myocardial infarction (AMI), hospitalization for acute heart failure (HF) and mortality (M). Results: The FP rate was 4, 5% (16P). Comparing to F0, P in group FP+ were younger (65, 1±2, 4 vs 70, 5±0, 6 years; p=0, 045), baseline wall motion abnormalities were more frequent (75, 0% vs 41, 6%; p=0, 009), had higher mean blood pressure values at rest (99, 3±5, 4 vs 82, 0±1, 3 mmHg; p=0, 004) and at peak stage (140, 3±5, 6 vs 102, 8±2, 3 mmHg; p<0, 001) and more often hypertensive response (37, 5% vs 7, 1%; p<0, 001). There were no significant differences regarding previous CA disease, medication or complete left bundle branch block. By multivariate analysis, only mean blood pressure values at rest (OR 0, 01; 95%CI 0, 005-0, 02; p=0, 003) and at peak stage (OR 0, 02; 95%CI 0, 000-0, 004; p=0, 003) were independente predictors of FP. During follow-up was observed: AMI (FP+: 12, 5% vs FP0: 1, 8%, p=0, 046), HF (FP+: 6, 3% vs FP0: 11, 5%, p=0, 44) and M (FP+: 6, 3% vs FP0: 6, 2%, p=0, 65). After adjustment for age, sex and comorbidities, there were no diferences between the groups regarding HF (p=0, 45) and M (p=0, 77), but the group FP+ mantained a higher rate of AMI (OR 0, 21; 95%CI 0, 065-0, 354; p=0, 005). Conclusion: A FP result on SE is associated with higher mean blood pressure values during the test and with higher rates of AMI during follow-up. This result on SE should therefore be faced as a risk marker for ischemic events and can identify P that may benefit from aggressive risk factor control and careful clinical follow-up.